Penguatan Pendidikan Lingkungan Hidup dan Pengembangan Rumah Bibit di Desa Ngesrepbalong untuk Konservasi Gunung Ungaran - Satya Budi Nugraha; Nana Kariada Tri Martuti; Tzabit Azinar Ahmad; Danang Dwi Saputro; Inaya Sari Melati (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Collaboration between the Village Government and various stakeholders to increase community participation in conserving the environment needs to be done. Ngesrepbalong Village, located in Limbangan District, Kendal Regency, has a wealth of diverse natural potential. This community service activity aims to strengthen knowledge and the role of the community in environmental conservation in their area. Activities are carried out using community education and consultation methods. The implementation of strengthening environmental education targets groups of teenagers and children. Activities include the introduction and practice of composting, planting trees, and bird watching. The hope is to strengthen the mindset of teenagers and children as future generations who participate in preserving nature. Meanwhile, the development of the Handarbeni Seedling House seeks to strengthen its role as a means of educating perennials and supporting the Mount Ungaran conservation program. Its activities include identifying the type and number of plant seeds and compiling plant barcodes containing local names, scientific names, plant benefits, and conservation status. These two programs are small efforts that need to be carried out sustainably to realize nature conservation in the forest environment, especially on the slopes of Mount Ungaran.